tan theta/sec thetha-1 + tan thetha/ sec thetha+1 = 2 cosec thetha
Answers
Answered by
0
Step-by-step explanation:
secθ−1
tanθ
+
secθ+1
tanθ
=2cosecθ
Taking the LHS of the above equation,
\frac{tan{\theta}}{sec{\theta}-1}+\frac{tan{\theta}}{sec{\theta}+1}
secθ−1
tanθ
+
secθ+1
tanθ
=\frac{tan{\theta}(sec{\theta}+1)+tan{\theta}(sec{\theta}-1)}{sec^{2}{\theta}-1}
sec
2
θ−1
tanθ(secθ+1)+tanθ(secθ−1)
=\frac{tan{\theta}sec{\theta}+tan{\theta}+tan{\theta}sec{\theta}-tan{\theta}}{sec^{2}{\theta}-1}
sec
2
θ−1
tanθsecθ+tanθ+tanθsecθ−tanθ
=\frac{2tan{\theta}sec{\theta}}{tan^{2}{\theta}}
tan
2
θ
2tanθsecθ
=\frac{2sec{\theta}}{tan{\theta}}
tanθ
2secθ
=2sec{\theta}cot{\theta}2secθcotθ
=2{\times}\frac{1}{cos{\theta}}{\times}\frac{cos{\theta}}{sin{\theta}}2×
cosθ
1
×
sinθ
cosθ
=\frac{2}{sin{\theta}}
sinθ
2
=2cosec{\theta}2cosecθ =RHS
Similar questions
English,
5 months ago
Social Sciences,
5 months ago
English,
10 months ago
Geography,
10 months ago
English,
1 year ago